2022
DOI: 10.33011/newlibs/11/12
|View full text |Cite
|
Sign up to set email alerts
|

What Role Do You Play? Faculty Perceptions of Librarian-led Information Literacy Instruction

Abstract: This study explored faculty perceptions of librarian-led information literacy instruction using Interpretative Phenomenological Analysis. Semi-structured interviews were conducted with six faculty who taught undergraduate general education courses. The emergent theme of this study was that faculty believe their role in teaching information literacy differs from librarians. The participants thought faculty were responsible for teaching information literacy through direct instruction and assigning course work, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Direct instruction and coursework assignments were considered the prerogative of the faculty and librarians were in charge of the research process. The results of the study also show the necessity of collaboration between educators (Breland, 2022).…”
Section: Discussionmentioning
confidence: 68%
“…Direct instruction and coursework assignments were considered the prerogative of the faculty and librarians were in charge of the research process. The results of the study also show the necessity of collaboration between educators (Breland, 2022).…”
Section: Discussionmentioning
confidence: 68%
“…The development of information literacy in the field of law can be compared to the development of information literacy in universities and higher education libraries worldwide. As in scholarship in other fields, most researchers have indicated that, due to the development of information and communication technology and changes in the educational environment, law libraries must adapt their information services and apply information literacy programmes as much as possible (Callister, 2003;Breland, 2022;Dell, 2019;Garingan, 2021;Kaplan and Darvil, 2011;Naveed and Shah, 2023;Webber and Johnston, 2000). Jayasuriya and Brillantine (2008) state that with each wave of innovation in legal publishing and the development of information technology, law librarians must re-evaluate their information services for students.…”
Section: Information Literacy In the Field Of Lawmentioning
confidence: 99%